Transient Receptor Potential Vanilloid1 (TRPV1) Channel Opens Sesame of T Cell Responses and T Cell-Mediated Inflammatory Diseases - Xiao, Tengfei; Sun, Mingzhong; Kang, Jingjing; Zhao, Chuanxiang (Frontiers in Immunology, 2022)
Transient receptor potential vanilloid1 (TRPV1) was primarily expressed in sensory neurons, and could be activated by various physical and chemical factors, resulting in the flow of extracellular Ca2+ into cells. Accumulating data suggest that the TRPV1 is expressed in some immune cells and is a novel regulator of the immune system. In this review, we highlight the structure and biological features of TRPV1 channel. We also summarize recent findings on its role in modulating T cell activation and differentiation as well as its protective effect in T cell-mediated inflammatory diseases and potential mechanisms.